2018
DOI: 10.5056/jnm17019
|View full text |Cite
|
Sign up to set email alerts
|

Interest of Anorectal Manometry During Long-term Follow-up of Patients Operated on for Hirschsprung's Disease

Abstract: Background/AimsAlthough many advances in the management of Hirschsprung's disease have recently been achieved, postoperative outcomes of these patients remain difficult in a non-negligible number of cases. Therefore, this study aims at investigating characteristics of anorectal manometry and its relationship with postoperative outcomes during long-term follow-up in Hirschsprung patients. MethodsPatients over 4 years of age operated on for Hirschsprung's disease were interviewed to complete detailed questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Tran reported that the prevalence of FI and constipation was 22.6% and 13.2%, respectively, in the enrolled 53 children following surgery for HD. The values of resting anal pressure and the maximum tolerated volume in incontinent patients were significantly lower than those in continent patients (36). Similar results were also reported by other researchers (37).…”
Section: High-resolution Anorectal Manometrysupporting
confidence: 91%
“…Tran reported that the prevalence of FI and constipation was 22.6% and 13.2%, respectively, in the enrolled 53 children following surgery for HD. The values of resting anal pressure and the maximum tolerated volume in incontinent patients were significantly lower than those in continent patients (36). Similar results were also reported by other researchers (37).…”
Section: High-resolution Anorectal Manometrysupporting
confidence: 91%
“…In this study, we found that 19.4% of soiling in the LCEPC procedure was higher than the LSGC procedure, and the anal resting pressure was significantly lower in the LCEPC group. Tran et al ( 23 ) reported that the internal and external anal sphincters contributed to 55.0% and 35.0% of the anal resting pressure, respectively. Therefore, the decreased anal resting sphincter pressure was related to the partial resection of the internal anal sphincter in the LCEPC procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Anorectal manometry (ARM) is a noninvasive and repeatable diagnostic test for the quantitative evaluation of anorectal function 1 . It has been widely used in the diagnosis of Hirschsprung's disease (HD), 2,3 functional constipation, 4‐6 and the evaluation of patients after anorectal surgery 7‐9 . It is well known that there is rapid body growth between infancy and childhood; however, neither the physiological or functional development of the anorectal canal during this period is well understood, and the reference values for pediatric manometry are remain to be validated.…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been widely used in the diagnosis of Hirschsprung's disease (HD), 2,3 functional constipation, 4-6 and the evaluation of patients after anorectal surgery. [7][8][9] It is well known that there is rapid body growth between infancy and childhood; however, neither the physiological or functional development of the anorectal canal during this period is well understood, and the reference values for pediatric manometry are remain to be validated. Previous research 10,11 studied the relationship between anal function and age, but no consistent…”
mentioning
confidence: 99%